2006
DOI: 10.1111/j.1743-6109.2006.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

The tetrapeptide acetyl‐serine‐aspartyl‐lysine‐proline improves skin flap survival and accelerates wound healing

Abstract: The tetrapeptide acetyl-serine-aspartyl-lysine-proline (AcSDKP) has recently been recognized as a potent angiogenic factor. Given the importance of vascular blood supply in the process of tissue repair we have investigated the ability of AcSDKP to contribute to the repair of cutaneous injuries by using dorsal and abdominal skin flap models. Postoperative subdermal AcSDKP injections (5 microg/kg/injection twice a day for 3 days following flap elevation) prevented marginally perfused areas from undergoing necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…AcSDKP reportedly exhibits anti-fibrotic organ-protective effects in various experimental models (Fromes et al, 2006; Omata et al, 2006; Castoldi et al, 2013; Zuo et al, 2013). Additionally, we have reported that AcSDKP prevents mesangial matrix expansion in diabetic db/db mice (Shibuya et al, 2005).…”
Section: Anti-fibrotic Effects Of Acsdkpmentioning
confidence: 99%
See 2 more Smart Citations
“…AcSDKP reportedly exhibits anti-fibrotic organ-protective effects in various experimental models (Fromes et al, 2006; Omata et al, 2006; Castoldi et al, 2013; Zuo et al, 2013). Additionally, we have reported that AcSDKP prevents mesangial matrix expansion in diabetic db/db mice (Shibuya et al, 2005).…”
Section: Anti-fibrotic Effects Of Acsdkpmentioning
confidence: 99%
“…AcSDKP (Liu et al, 2003; Wang et al, 2004; Fromes et al, 2006) and its precursor peptide, Tβ4 (Malinda et al, 1997; Huff et al, 2001; Koutrafouri et al, 2001; Philp et al, 2003) have been shown to enhance angiogenesis and exhibit anti-fibrotic effects associated with normalization of organ function (Smart et al, 2007). AcSDKP improves skin flap survival and accelerates wound healing (Fromes et al, 2006).…”
Section: Acsdkp and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The view that many pathological conditions could benefi t from the inhibition or stimulation of vasculogenesis and angiogenesis was supported by multiple investigations [63][64][65]. However, some apparently contradictory fi ndings have marked EPC research.…”
Section: Endothelial Progenitor Cells: Classical Neighborhood Cellsmentioning
confidence: 99%
“…AcSDKP prevents primitive hematopoietic cells entry into S-phase of a cell cycle [11,12]. The recent studies revealed that AcSDKP induces angiogenesis and improves wound healing, as well as heart regeneration after ischemia [13][14][15]. The significant increase of serum levels of tetrapeptide was observed in patients with leukemia [16].…”
Section: Introductionmentioning
confidence: 99%